Ovarian gonadoblastoma with dysgerminoma in a girl with 46,XX karyotype 17a-hydroxylase/17, 20-lyase deficiency: A case report and literature review - Yin, Min; Yang, Jiaxin; Tian, Qinjie; Zhang, Xinyue (Frontiers in Endocrinology, 2022)
17α‑hydroxylase/17,20‑lyase deficiency (17-OHD), caused by mutations in the gene of the cytochrome P450 family 17 subfamily A member 1 (CYP17A1), is a rare type of congenital adrenal hyperplasia (CAH), usually characterized by cortisol and sex steroid deficiency combined with excessive mineralocorticoid. Gonadoblastoma is a relatively rare ovarian tumor that is frequently seen among patients with 46,XY gonadal dysgenesis. Rarely have they been reported in female patients with normal 46,XX karyotype. Here, we report an interesting case of an 11-year-old Chinese girl who presented acute abdominal pain that was later attributed to tumor rupture of right ovarian gonadoblastoma with dysgerminoma. Further evaluations revealed hypertension and hypokalemia. Hormonal findings showed increased progesterone, hypergonadotropic hypogonadism, and low cortisol levels. Her chromosome karyotype was 46,XX without Y chromosome material detected. Genetic analysis revealed that the patient had a homozygous pathogenic variant c.985_987delTACinsAA (p.Y329Kfs*90) in exon 6 of the CYP17A1 gene and that her parents were all heterozygous carriers of this pathogenic variant. Due to the variable clinical manifestations of 17-OHD, meticulous assessment including genetic analysis is necessary. Further study is warranted to unravel the mechanism of gonadoblastoma in a patient with normal karyotypes.